Why it happened and how it could have been different : a comparison of causal and counterfactual thinking - McEleney, Alice (Trinity College (Dublin, Ireland). School of Psychology, 2000)
The aim of this thesis was to compare two pervasive forms of human thinking : causal thinking about why an outcome happened (e.g., "I failed because I didn’t try") and counterfactual thinking about how an outcome could have been different (e.g., "I wouldn’t have failed if I had tried"). We report nine experiments designed to test the hypothesis that causal thoughts are concerned with the prediction of outcomes, whereas counterfactual thoughts are concerned with their prevention.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin